An evaluation of library services offered to preschoolers in selected private schools in Metro Manila with implications to preschool library standardization - Surla, Selina B.; Faderon, Rosalie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2002)
The onset of the new millennium has brought about further advances in information technology. These are seen and felt by everyone, everywhere, and are most evident in the workplace and in the learning arena. These have, in fact, affected even the very young school children. Thus, it is not a surprise that preschools nowadays have their own libraries. However, with the DECS lacking recommended minimum preschool library standards, most preschools are having a difficult time setting-up libraries for their students.
This study evaluated the operational systems of three (3) preschools which are known to have libraries, the Colegio San Agustin Kinder-Prep Division, the Miriam College Child Study Center and the Xavier School Early Education Department. Similarities found between all three schools were then compared with the DECS recommended minimum library standards for elementary schools. After which, recommendations were done on a point by point basis.
Points emphasized were the physical set-up of each library, including space allocations for various learning areas; collections which are both book and non-book in nature, and for use of both students and teachers; furniture and equipment, how the preschool library should be designed in order to make its atmosphere comfortable and homey, yet conducive to learning; library management and staff, including those who are eligible to become librarians and library assistants; and lastly, librarians' tools and materials, including the more important cataloging and classification tools.
Finding showed that most preschools follow the recommended minimum standards for elementary schools. These schools also have certain variations in their methods of orienting their students on how to use the library. There are also many different possibilities on how to set-up a library for preschool students. All the schools which participated in the study had adjustments done on their furniture and interior decorations. This makes each preschool library a relaxing and enjoyable place to visit for the children because almost everything is custom-made to be kid-friendly; be it visual aids, bulletin boards, toys, book and non-book materials, and even their furniture. Bright colors such as red, yellow, green and blue are used to liven up the preschool libraries.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Libraries and preschool children